Building the Business Case for Public Health Information Systems. Issue 6 (November 2016) - Baker, Edward L.; Brand, William; Davidson, Arthur; LaVenture, Martin; Singletary, Vivian; Smith, Perry
Abstract : This article describes building the business case for public health information systems.